Manajemen Risiko dalam Bisnis Peternakan: Manajamen Risiko Produksi dan Teknis di Chiken Gendut Farm - Pratama, Okka Putra; Kurniyanto, Ifan Rizky; Wijayanti, Dian Eswin (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Chicken Gendut Farm is a farm that focuses on breeding broiler chickens. During the production period, this farm had the most significant problems, such as disease attacks, poor-quality Day-Old Chicken (DOC), and extreme weather that could cause death in chickens. This study aims to 1) Identify sources of production risk at Chicken Gendut Farm, 2) Analyse the level of production risk opportunities, risk impacts, and risk maps, and 3) Formulate appropriate risk handling strategies for Chicken Gendut Farm. The data analysis methods used were Fishbone analysis, Z-Score, and Value at Risk (VaR). The results showed that Chicken Gendut Farm identified sources of production risk caused by internal and external business factors. Risk mapping shows four risks in quadrant I: poor air or temperature in the cage, disease attack, extremely hot weather, and poor DOC quality. Risk management strategies that Chicken Gendut Farm can carry out are preventive strategies, such as increasing worker discipline in cage management, separating sick chickens, maintaining cage cleanliness, limiting access in and out of the cage, and spraying disinfectant spray for people who enter the cage.